Attitude and knowledge of women about menopause and hormone replacement therapy - Roya Faraji; Maryam Asgharnia; Fatemeh Hosseinzadeh; Seyedeh Fatemeh Dalil heirati; Atefeh Emadi (Journal of Holistic Nursing and Midwifery)
Abstract: Introduction: Menopause is one of four crises of women s life that predispose for many of hormonal change. Menopause is the stage of women s life in which ovarian function is terminated and level of estrone hormones that are secreted form ovarianes, severely reduced. Menopause accompanied with remarkable somatic and psychologic changes. The most important of these changes in long time causes evidence of cardiovascular disease, osteoporosis, bone fracture and even Alzhemier. Regarding to knowledge and attitude towards menopause and hormone replacement therapy in women can help to improve their performance and reduce the severity of these effects. Therefore, pay special attention to increase awareness and provide good service before and after the menopause. Objective: the aim of this study is to evaluate attitude and knowledge of women about menopausal symptoms, associated factors, side effects and hormone replacement therapy in menopausal periods. Material and methods: this is a cross sectional-descriptive study has done in 277 women aged 45 years or more which have been visited in hospital s clinics at Rasht city in 2007. Data were obstetrician history and patient s information about menopouse, its symptoms, side effect and female attitude for hormone therapy. These data were analysed by T test and Chi-square and spss10 software. Results: 32.1% of 277 women had high knowledge about predisposing factors of menopause 60.7%(168) were well informed about menopausal signs ,75.5%(209)were agreed about hormone therapy, between attitude and knowledge of inducing factors ,also attitude and knowledge of menopausal signs were direct correlation(p<0.0001 - P<0.0001). Among education level, socio-economic situation, less number of parity and knowledge of Predisposing factors were significant relation (P<0.0001 - p<0.0001 and p= 0.025) Also level of knowledge about menopausal signs, education status, socio-economic situation History of abortion and kind of contraception had significant relation (p<0.0001 - p<0.0001- p=0.027 and p=0.036). Education, socio-economic situation, higher age group had significant relation with hormon replacement therapy (p<0.0001 - p<0.0001 - and p=0.001). Conclusion: Socio-economic situation and educational level had direct effect on menopausal signs and risk factors, so by improving of women education and socio-economic situation can improve female s awareness or passing this period of life without any crises